The Enhancement of Learning Mathematic’s Motivation by Using Application of Quantum Learning Model Teaching - Trisnawati Trisnawati; Wiwin Rita Sari; Bernadhita Herindri S. Utami (SAINTIS Publishing, 2019)
This study aims to describe the effectiveness of Quantum Teaching learning model on mathematics learning in terms of aspects of student learning motivation. The type of experiment in this study was quasi experimental research (quasi alphabets experiment) and experimental design that used up was one-Group Pretest-Posttest-. The population in this research was the whole grade VIII of SMPMuhammadiyah 1 Yogyakarta, which was grade VIII-D as sample. The independent variable in this study was a model of Quantum Learning Teaching and the dependent variable in this study was the studentmotivation mathematic’slearning. The instrument used was the student learning motivation questionnaire. To test the effectiveness of Quantum Learning Teaching model, the data were analyzed by using one sample t-test. The results showed that the model of Quantum Learning Teaching effective motivational aspects of learning math.